(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
This article presents an analytical and review study of membrane processes and equipment used for juice purification and concentration in the food industry. Special attention is given to technological innovations and the role of intellectual property in protecting membrane solutions. The paper highlights current trends, practical applications, and patent landscape relevant to membrane technologies in juice processing.